ПСИХРОФІЛЬНІ БАКТЕРІЇ РОДІВ ALTEROMONAS І PSYCHROBACTER, ВИДІЛЕНІ З ВОДИ ЧОРНОГО МОРЯ - Онищенко, О. М.; Кіпріанова, О. А.; Ярошенко, Л. В. (Marine Ecological Journal, 2023)
On the basis of the phenotypic analysis data and partial sequences of 16S rRNA gene seven strains of halophilic marine bacteria isolated from the Black Sea water have been assigned to extremal Antarctic species Psychrobacter glacincola (4 strains) and Alteromonas stellipolaris (3 strains). Being as a whole similar in their properties to Antarctic isolates, the Black Sea strains had some differences in ability to growth at higher temperatures, resistance to lower concentration of NaCl and assimilation of some carbon sources.